2021
DOI: 10.1001/jamanetworkopen.2021.25846
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Hospital Length of Stay in High-risk Populations

Abstract: Key Points Question Which hospital-led interventions are associated with reducing length of stay (LOS) for high-risk populations? Findings In this systematic review including 19 systematic reviews, 8 strategies for reducing LOS in high-risk populations were identified: discharge planning, geriatric assessment, medication management, clinical pathways, interdisciplinary or multidisciplinary care, case management, hospitalist services, and telehealth. Interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 56 publications
6
67
0
Order By: Relevance
“…32,33 In term of patients' related factors, previous studies have shown that old age, patient with multiple comorbidities including chronic heart failure, stroke, and soft tissue infection at increased risk of prolonged length of hospital stay. 34,35 Our study has shown that the majority of patients were hospitalized with circulatory and respiratory systems diseases. Pneumonia and exacerbations of chronic lung disease were among the most common diagnoses, with a median length of hospital stay of 6 days, which is higher than the reported length of hospital stay in similar health settings (i.e.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…32,33 In term of patients' related factors, previous studies have shown that old age, patient with multiple comorbidities including chronic heart failure, stroke, and soft tissue infection at increased risk of prolonged length of hospital stay. 34,35 Our study has shown that the majority of patients were hospitalized with circulatory and respiratory systems diseases. Pneumonia and exacerbations of chronic lung disease were among the most common diagnoses, with a median length of hospital stay of 6 days, which is higher than the reported length of hospital stay in similar health settings (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…5,9,41,42 Also, geriatric assessment for old patients, implementing of clinical pathways for management of common diagnoses such as heart failure, medications for patients with polypharmacy, and case management may reduce length of hospital stay. 34,43 This study has many strengths. It is one of the few studies from the Middle East Region where the expanding population puts extreme pressure on health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, as many previous improvement studies were limited by complex interventions or cumbersome implementations, and it has been suggested that team-based care approaches would have limited success. 19,[28][29][30] Given the clinical setting with a heterogeneous patient population, this nationwide large-scale study, showing high tool use and systematic assessment of outcomes with no missing data, may fill an important gap in the current evidence about the effectiveness of interprofessional-led discharge planning to reduce LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have examined LOS predictors to inform intervention and targeting strategies [4,5,[7][8][9]. A recent systematic review found that for patients with medically complex conditions, discharge planning, medication management, and interdisciplinary care teams were associated with inconsistent outcomes (LOS, readmissions, mortality) across populations [31]. There are no systematic reviews studying interventions for patients with socioeconomic risk; 70% of our admissions derive from a high deprivation inner-city population [32].…”
Section: Discussionmentioning
confidence: 99%